Analisis Sistem Pengendalian Internal terhadap Akuntansi Persediaan Barang pada Indomaret Dwikora 2 Palembang - Nisa, Nur Hikmatu; Indriani, Poppy (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The problem that occurs in this company is the frequent loss of inventory. Therefore this study aims to determine the procedure for receiving, issuing goods and to evaluate the internal control system for inventory accounting at Indomaret Dwikora 2 Palembang. This study uses qualitative data analysis and data obtained through observation, interviews and documentation. From the results of the study, it can be concluded that the internal control system implemented by the company has not been running effectively and efficiently because there are several elements of internal control that have not gone well, such as the absence of strict separation of store functions and warehouse functions and goods inspection transactions. implemented by one function only. In addition, regular employee rotation has not been carried out, in warehouses and Indomaret stores there are still several CCTVs whose cameras are blurry and even turn off and there is also no monitoring function that aims to monitor consumers who shop at Indomaret stores so that they can anticipate acts of theft and the like..